2013
DOI: 10.1161/hypertensionaha.113.01708
|View full text |Cite
|
Sign up to set email alerts
|

Female-Specific Hypertension Loci on Rat Chromosome 13

Abstract: A 3.7 Mb region of rat chromosome 13 (45.2–49.0 Mb) affects blood pressure (BP) in females only, indicating the presence of gender-specific BP loci in close proximity to the Renin locus. In the present study, we used a series of Dahl salt-sensitive/Mcwi (SS)-13 Brown Norway (BN) congenic rat strains to further resolve BP loci within this region. We identified 3 BP loci affecting female rats only, of which the 2 smaller loci (line9BP3 and line9BP4) were functionally characterized by sequence and expression anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

5
4

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 64 publications
1
12
0
Order By: Relevance
“…Fluorescence microscopy experiments confirmed that the Mas1 receptor antibody (Santa Cruz, sc-135063) epitope was intracellular (Supplemental Figure I). Signaling complexes were then verified for presence of Mas1 by immunoblot (Figure 2B, Supplemental Figure II) according to previous protocols 2225 using rabbit anti-rat Mas1 primary antibody (Santa Cruz, sc-135063) at 1:1000 and secondary HRP-conjugated goat anti-rabbit IgG antibody (BioRad) at 1:2000, as well as in the raw MS/MS data (Supplemental Figure II). In the Ang-(1-7) stimulated RMVEC signaling complexes, 50 proteins were identified as significantly increased (p<0.05, n=8 plus a technical replicate, 16 total MS runs) versus non-stimulated RMVECs after application of stringent filters (Figure 2C, Table 1, Supplemental Table I).…”
Section: Resultsmentioning
confidence: 99%
“…Fluorescence microscopy experiments confirmed that the Mas1 receptor antibody (Santa Cruz, sc-135063) epitope was intracellular (Supplemental Figure I). Signaling complexes were then verified for presence of Mas1 by immunoblot (Figure 2B, Supplemental Figure II) according to previous protocols 2225 using rabbit anti-rat Mas1 primary antibody (Santa Cruz, sc-135063) at 1:1000 and secondary HRP-conjugated goat anti-rabbit IgG antibody (BioRad) at 1:2000, as well as in the raw MS/MS data (Supplemental Figure II). In the Ang-(1-7) stimulated RMVEC signaling complexes, 50 proteins were identified as significantly increased (p<0.05, n=8 plus a technical replicate, 16 total MS runs) versus non-stimulated RMVECs after application of stringent filters (Figure 2C, Table 1, Supplemental Table I).…”
Section: Resultsmentioning
confidence: 99%
“…Within the region, it is also possible that other nonsynonymous variants and intergenic variants have functional consequences beyond the limitations of prediction software. Thus, validating these candidates genes will likely require further narrowing of the QTL by congenics (26, 50, 51), gene expression analysis, and/or directly testing candidates by gene-editing (20, 52, 53), all of which we have done previously for other disease loci (see below for description).…”
Section: Discussionmentioning
confidence: 99%
“…29 It is also possible that multiple causative variants co-segregate at the 830 kb locus, as we have demonstrated previously for other hypertension loci. 15, 23, 30 However, future studies targeting specific genes or further reducing the congenic interval will be necessary to localize the causative variant(s).…”
Section: Discussionmentioning
confidence: 99%